2002
DOI: 10.1302/0301-620x.84b3.12261
|View full text |Cite
|
Sign up to set email alerts
|

The Exeter universal cemented femoral component at 8 to 12 years: A study of the first 325 hips

Abstract: W e describe our experience with the implantation of 325 Exeter Universal hips. The fate of every implant was known. The procedures were undertaken by surgeons of widely differing experience. At follow-up at 12 years, survivorship with revision of the femoral component for aseptic loosening as the endpoint was 100% (95% CI 98 to 100). Survivorship with revision of the acetabular component for aseptic loosening as the endpoint was 96.86% (95% CI 93.1 to 98.9) and that with any reoperation as the endpoint 91.74%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
99
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(115 citation statements)
references
References 24 publications
(29 reference statements)
10
99
0
6
Order By: Relevance
“…Despite this, the literature on its survival is sparse. 14,29,30 This is in stark contrast to the Exeter design, from which the CPT was derived, which has excellent clinical and radiological followup in both its originating centre [1][2][3][4][5] and elsewhere. 6,7 This study follows the same cohort of patients previously reported at a minimum of ten years post-operatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, the literature on its survival is sparse. 14,29,30 This is in stark contrast to the Exeter design, from which the CPT was derived, which has excellent clinical and radiological followup in both its originating centre [1][2][3][4][5] and elsewhere. 6,7 This study follows the same cohort of patients previously reported at a minimum of ten years post-operatively.…”
Section: Discussionmentioning
confidence: 99%
“…The impressive survival of collarless polished double tapered femoral components has been demonstrated in originator series, [1][2][3][4][5] in nonoriginator series 6 and non-teaching centres 7 and in registry data. 8,9 There have been predictable patterns of subsidence at the stemcement interface, 10 a factor that has been suggested to confer stability to the stem 11 and provide protection to the cement-bone interface.…”
mentioning
confidence: 99%
“…The HSS hip score improved from an average of 16.7 points (range 12-32) preoperatively to 37.8 points (range [28][29][30][31][32][33][34][35][36][37][38][39][40] postoperatively at an average follow-up of 6.13 years (range 4-8.5) (P<0.0001) ( Table 1). The clinical results at the last follow-up in the 64 living patients was excellent in 61 patients, and good in three.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Longterm series and systematic analyses have supported the use of cemented stems as a legitimate alternative to noncemented stems from a clinical and economic perspective [1,5,8]. However, there are ongoing reports [3,7] of higher than acceptable long-term aseptic loosening rates for some cemented stems, including the specific ''shapeclosed'' stem design that was the subject of this study.…”
Section: Onsistently Excellent Clinicalmentioning
confidence: 91%